Different MHC class I cell surface expression levels in diverse chicken lines, associations with B blood group, and proposed relationship to antigen-binding repertoire - Michael Kaiser; Jim Kaufman; Susan J. Lamont (Poultry Science)
The Major Histocompatibility Complex (MHC) is a cluster of genes with primarily immune-related functions. The MHC class I genes are responsible for self- versus non-self-recognition and viral antigen presentation to T lymphocytes. The chicken MHC class I protein binds its cognate antigen(s) over a repertoire spectrum ranging from promiscuous (generalist) to fastidious (specialist). The MHC class I protein expression level at the cell surface is inversely related to the promiscuity of its peptide-binding repertoire. In our study, erythrocytes from 6 diverse and highly inbred lines of chickens, a closed broiler line, and a highly advanced intercross line were evaluated for MHC class I antigen expression level by flow cytometry using monoclonal antibodies to chicken MHC class I molecules. In chickens, the B blood group antigens include the MHC class I antigen expressed from the MHC. Thus, the B blood group has historically been used as a genetic marker for Marek's Disease virus response. Erythrocytes of the inbred lines were blood typed by serology. The B21 blood type is widely recognized as relatively resistant to Marek's disease and regarded as an MHC class I generalist with low MHC class I expression. The Spanish line, which types serologically as B21.1 (similar to B21), was the lowest MHC class I expressing line. The two sublines (B5.1 and B15.2) of the Fayoumi breed, which significantly differed in their MHC class I expression, also differ in response to multiple pathogens. These defined genetic lines of chickens, with distinct MHC class I expression levels, provide an excellent platform to further interrogate the hypothesis of high or low MHC class I expression (antigenic specialists or generalists, respectively) determining diverse responses to pathogens.